Molecular Volume Effects on the Dynamics of Polymerized Ionic Liquids and their Monomers. (1st September 2015) - Choi, U Hyeok; Mittal, Anuj; Price, Terry L.; Lee, Minjae; Gibson, Harry W.; Runt, James; Colby, Ralph H.
Abstract: The dependences of the glass transition temperature and the dielectric constant on molecular volume of the repeat unit for polymerized ionic liquids, the monomers they were polymerized from and simple ionic liquids, are reviewed and compared. The ionic conductivities of these materials and the frequencies at which ionic rearrangements occur are shown to be controlled by their glass transition temperatures. The ionic conductivity is proportional to the product of dielectric constant and ionic rearrangement frequency, with the proportionality constant determined by the molecular volume of the repeat unit.